Inequality, Socio-cultural Differentiation and Social Structures in Africa Beyond Class - Neubert, Dieter (Frontiers of Globalization, 2019)
This book contends that conventional class concepts are not able to adequately capture social inequality and socio-cultural differentiation in Africa. Earlier empirical findings concerning ethnicity, neo-traditional authorities, patron-client relations, lifestyles, gender, social networks, informal social security, and even the older debate on class in Africa, have provided evidence that class concepts do not apply; yet these findings have mostly been ignored. For an analysis of the social structures and persisting extreme inequality in African societies - and in other societies of the world - we need to go beyond class, consider the empirical realities and provincialise our conventional theories. This book develops a new framework for the analysis of social structure based on empirical findings and more nuanced approaches, including livelihood analysis and intersectionality, and will be useful for students and scholars in African studies and developmentstudies, sociology, social anthropology, political science and geography.